Stopping of Mycophenolic Acid in Kidney Transplant Recipients for 2 Weeks Peri-Vaccination Does Not Increase Response to SARS-CoV-2 Vaccination—A Non-randomized, Controlled Pilot Study - Regele, Florina; Heinzel, Andreas; Hu, Karin; Raab, Lukas; Eskandary, Farsad; Faé, Ingrid; Zelzer, Sieglinde; Böhmig, Georg A.; Bond, Gregor; Fischer, Gottfried; Oberbauer, Rainer; Reindl-Schwaighofer, Roman (Frontiers in Medicine, 2022)
Kidney transplant recipients (KTR) are at risk for severe COVID-19. However, vaccine response in this population is severely impaired with humoral response rates of 36-54% and 55-69% after two or three doses of SARS-COV-2 vaccines, respectively. The use of anti-proliferative agents such as with mycophenolic acid (MPA) or azathioprine (AZA) have been identified as risk factors for vaccine hypo-responsiveness. We hypothesized that in vaccine non-responders to at least three previous vaccine doses, pausing of MPA or AZA for one week before and one week after vaccination would improve humoral response. We conducted an open-label, non-randomized controlled pilot study including 40 KTR with no detectable humoral response after three or four previous vaccine doses. Primary endpoint was seroconversion following SARS-CoV-2 vaccination. MPA and AZA was paused in 18 patients one week before until one week after an additional vaccine dose while immunosuppression was continued in 22 patients. There was no difference in the humoral response rate between the MPA/AZA pause group and the control group (29% vs 32%, p>0.99). At 4 weeks after vaccination the geometric mean antibody levels in the MPA/AZA pause and control group were 0.7 U/mL and 1.1 U/mL (p= 0.591), respectively. Renal function in the MPA/AZA pause group remained stable. Pausing of MPA/AZA for two weeks peri-vaccination did not increase the rate of seroconversion in kidney transplant. However, one in three KTR without humoral immune response to at least three previous vaccinations developed antibodies after an additional vaccine dose supporting continued vaccination in non-responders.